Co-existence of ANCA–associated vasculitides with immune-mediated diseases: a single-center observational study - Masiak, Anna; Jassem, Ewa; Dębska-Ślizień, Alicja; Bułło-Piontecka, Barbara; Kowalska, Bożena; Chmielewski, Michał (Rheumatology international, 2024)
Background Antineutrophil cytoplasmic antibody-associated vasculitides (AAV) is a group of systemic necrotizing small vessel autoimmune diseases, with microscopic polyangiitis (MPA) and granulomatosis with polyangiitis (GPA) being the two most common. The co-existence of AAV with different immune-mediated diseases (autoimmune disesases - AID) might affect the clinical presentation of the primary disease. The purpose of the study was to assess the co-existence of AAV with AID and to investigate whether it affects the characteristics and the course of AAV. Methods A retrospective single-center study was performed to identify patients with a diagnosis of MPA or GPA and concomitant AID, and to investigate their clinical features and characteristics. The group consisted of consecutive unselected AAV patients treated at a large university-based hospital, since 1988 with follow-up until 2022. Results Among 284 patients diagnosed either with GPA (232) or MPA (52), 40 (14,1%) had co-existing AIDs. The most frequent were: Hashimoto thyroiditis (16 cases), rheumatoid arthritis (8 cases), followed by psoriasis (6 cases), pernicious anemia (3 cases), and alopecia (3 cases). Patients with autoimmune comorbidities had a significantly longer time between the onset of symptoms and the diagnosis (26 vs. 11 months, p < 0.001). Laryngeal involvement (20.0% vs. 9.0%, p = 0,05), peripheral nervous system disorders (35.0% vs. 13.9%, p < 0.001), and neoplasms (20.0% vs. 8.6%, p = 0,044) were more common in patients with AID comorbidities, compared to subjects without AID. In contrast, renal involvement (45.0% vs. 70.9%, p = 0.001) and nodular lung lesions (27.5% vs. 47.5%, p = 0.044) were significantly less frequent in patients with co-morbidities. Following EUVAS criteria, patients with autoimmune co-morbidities had a generalized form of the disease without organ involvement (52.5% vs. 27.2%, p = 0.007), while the others had a higher percentage of generalized form with organ involvement (38.3% vs. 20.0%, p = 0.007). Conclusions The coexistence of AAV with different autoimmune diseases is not common, but it might affect the clinical course of the disease. Polyautoimmunity prolonged the time to diagnosis, but the AAV course seemed to be milder. Particular attention should be paid to the increased risk of cancer in these patients. It also seems reasonable that AAV patients should receive a serological screening to exclude the development of overlapping diseases.